Nutritional composition and amino acid profile of a sub-tropical red seaweed Gelidium pusillum collected from St. Martin’s Island, Bangladesh - Siddique, Mohammad Abdul Momin; Khan, Md Shahzad Kuli; Bhuiyan, Md Khurshid Alam (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Nutritional fact study has prime importance to make the species edible and commercially viable to the food consumers. The proximate chemical composition and amino acid profile of Gelidium pusillum were studied to understand the nutritional status. The red seaweed Gelidium pusillum was rich in dietary fibre (24.74 ± 1.05%), lipid (2.16 ± 0.61%) and ash content (21.15 ± 0.74%). The mean protein content (11.31 ± 1.02% DW) was within the range of 10-47% for green and red seaweeds and this range was higher than Gracilaria cornea (5.47% DW), Gracilaria changgi (6.90% DW) and Eucheuma cottonii (9.76% DW). Gelidium pusillum was found to contained all the essential amino acids, which accounted for 52.08% of the total amino acids. Tyrosine (26.2 mg g-1 protein), methionine (15.8 mg g-1 protein) and Lysine (48.3 mg g-1 protein) were the limiting amino acid of Gelidium pusillum. However, the levels of other essential amino acids were above the FAO/WHO requirement pattern (EAA score ranged from 1.14 to 1.62). Aspartic and glutamic acids constituted a substantial amount of the total amino acids (24.68% of total amino acid). The result from this study suggested that Gelidium pusillum could be utilized as a healthy food item for human consumption.